GLOBALIZATION AS A FACTOR FOR SELF-DIRECTED DEVELOPMENT OF STUDENTS - Petr N. Osipov; Yuliya N. Ziyatdinova (Высшее образование в России, 2016)
The paper describes the newly appearing trend showing that due to globalization any person can receive education, find employment opportunities and live in any country of the world on condition he is a competitive specialist and he can adjust to new conditions. Today, every person can play his social role in a certain country, and, at the same time, be a ‘global citizen’ who thinks at a ‘planetary scale’. Therefore, it is important that a person should contribute to his selfHdirected personal and professional development, find independent solutions of social and professional problems, and make independent decisions under the rapidly changing circumstances. University education should encourage every person to promote selfHdirected education and to increase individual responsibility for the results. The authors give a number of tools to provide the solutions for the problems raised.